Dampak Pengumuman Sovereign Credit Ratings Indonesia oleh Lembaga Pemeringkat Fitch pada Imbal Hasil Saham Perbankan yang terdaftar di Bursa Efek Indonesia - , Novrika Riantony, Prof. Dr. Slamet Sugiri, M.B.A., Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main purpose of this research is to analyze the effect of sovereign credit rating announcement from Fitch Rating Agency on 15 December 2011 to the banking stock return, measured by abnormal return. Data on this research is secondary data collected from Indonesian Stock Exchange (www.idx.co.id). The population is stock from national banking sector represented by 27 listed stock. Event study analysis is used to analyse the information content from the announcement, in combination with abnormal return as measurement indicator. This study finds that the announcement contains information content which contributes to the changes in abnormal stock return. However, the impact is insignificant.